Effect of fixed value positive end expiratory pressure valves on canine thoracic volume and atelectasis. (22nd July 2017) - Allison, A.; Huizing, X.; Jolliffe, C.; Schaafsma, I.
Abstract : Objectives: The objective of this study was to investigate whether a fixed 10 cm H2 O positive end‐expiratory pressure valve would increase the aeration of, and reduce atelectasis formation in, the lungs after induction of anaesthesia in dogs undergoing thoracic CT. Materials and Methods: 28 dogs were paired based on breed, bodyweight and body condition score and then randomly allocated to either Group Z (0 cm H2 O) or Group P (10 cm H2 O positive end‐expiratory pressure valve) immediately after the induction of anaesthesia. All patients received a standardised anaesthetic protocol, and their lungs were manually hyperventilated before image acquisition. Cardiorespiratory parameters were recorded every 5 minutes. Total lung volume, lung density and degree of atelectasis were determined for each dog from the acquired images. Results: The 10 cm H2 O positive end‐expiratory pressure valve significantly increased lung volume (mL/kg) (Group Z: 52 ±14; Group P: 83 ±17; P<0·001) whilst significantly reducing lung density (Hounsfield units) (Group Z: −775 ±30; Group P: −856 ±22; P<0·001) and the amount of atelectasis (P=0·004). Dogs in Group P had significantly higher end‐tidal carbon dioxide (P<0·05), but there was no difference between the groups for respiratory rate or any cardiovascular variable. Clinical Significance: A fixed‐value positive end‐expiratory pressure valve provides a simple, cost‐effective technique for improving expiratory thoracic CT studies by increasing lung volume and decreasing atelectasis formation.